PENGARUH PENGGUNAAN MOBILE BANKING TERHADAP MINAT NASABAH DALAM BERTRANSAKSI MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL - Rian Maulana; Iskandar Iskandar; Masrura Mailany (UIN Ar-Raniry, 2018)
This research was conducted to see how the effect of using Mobile banking on Customer Interests in Transacting with the Acceptance Model technology and also seeing what happened to transactions. The results of this study resulted in the observation variable usefulness (X) has a significant effect on the interest in transacting (Y) where the coefficient is 11.127 with a significance level of 0.002 and the regression coefficient of use (X) of 0.640 each increase in 1% usability value, the value of Interest increases amounting to 0.640. The regression coefficient is positive, it can be called that the direction X variable towards Y is positive.